Biogeographical regionalisation of the Andean region - Morrone, Juan J. (Zootaxa, 2015)
A biogeographic regionalisation of the Andean region is proposed as a hierarchical classification of sub-regions, provinces, sub-provinces and districts. It is based on biogeographic analyses of terrestrial plant and animal taxa, and seeks to provide universality, objectivity and stability. The Andean region is currently comprised of the Central Chilean, Subantarctic and Patagonian sub-regions and the South American transition zone, 15 provinces, five sub-provinces and 81 districts. Complete synonymies and brief descriptions of the areas are provided, as well as the endemic taxa that diagnose the provinces.